Dietary intake and knowledge of fermented food products among university students - Sharareh Hekmat; Latifeh Ahmadi (Exploration of Foods and Foodomics)
Aim: This study examined the knowledge and consumption patterns of fermented foods among undergraduate students, comparing those enrolled in Food and Nutrition programs with students from other academic disciplines. Methods: A cross-sectional survey of 328 Canadian university students gathered demographic data and assessed familiarity, understanding, and intake of fermented food products. Results: While 78% of students reported familiarity with fermented foods, only 23% could accurately define fermentation. Students in Food and Nutrition programs demonstrated stronger knowledge, correctly answering 67% of related questions versus 62% in other disciplines (p = 0.07; 90% CI). Consumption rates were high overall, with 96% of participants reporting they consumed fermented foods. Significant differences were found between groups in specific categories: fermented fruits and vegetables (p = 0.02), soybeans (p = 0.002), grains (p = 0.02), and meat products (p = 0.017). Regarding frequency, 36% of students consumed a variety of fermented foods weekly, while 30% reported monthly consumption. Conclusions: Cultural background, taste preference, and educational focus also appear to influence dietary behaviors. Enrollment in a Food and Nutrition program was linked to both higher knowledge and increased intake. To the best of our knowledge, this is the first Canadian study to explore differences in fermented food knowledge and consumption across academic disciplines. These results support the potential of education-based strategies to promote healthier dietary patterns and warrant further research across more diverse populations.